The effects of freezing rates on the quality of mangoes (Manifera indica, Linn.) - De Lima, Libia Setosa 1941-; Smith, Donald B. (1969)
Mango samples of varying sizes were frozen at 4 different freezing rates, represented by 4 freezing methods, namely, cabinet freezing at -10°F (-23.3°C), stationary plate freezing at -40°F (-40°C), immersion freezing in dichlorodiflouromethane and liquid nitrogen immersion freezing. Evaluation of the frozen samples were based on the amount of drip losses, histological examination and organoleptic assessment. Results of the study indicate that samples frozen at -10°F (-23.3°C) in a cabinet freezer had a soggy texture and watery appearance. A decrease in drip loss and an involvement in texture, especially in the smaller mango pieces were achieved in products frozen -40°F (-40°C)in a stationary plate freezer. Consequently, an increased preference rating was given to samples frozen by this latter method. Immersion freezing in both dichlorodiflouromethane and in liquid nitrogen achieved samples comparable in appearance to fresh mango samples. Drip losses were further decreased by these methods, the effect being more marked with liquid nitrogen. Immersion in dichlorodiflouromethane resulted in a texture, similar to texture of fresh mangoes, while immersion in liquid nitrogen caused a certain brittleness in the texture of the thawed sample. Slight cracking was also observed in the liquid nitrogen-frozen samples. Leaching of the carotenoid pigments was noted during immersion freezing in dichlorodiflouromethane and a slight loss in flavor was detected by the panel in the samples so frozen.
Thesis (M.S. Food Science)--University of the Philippines, Diliman.
Keywords: Mango, Frozen